2020
DOI: 10.1016/j.psj.2020.09.043
|View full text |Cite
|
Sign up to set email alerts
|

Dietary effect of probiotics and prebiotics on broiler performance, carcass, and immunity

Abstract: This experiment was carried out to evaluate the effects of dietary addition of probiotics (Protexin) and prebiotics (active MOS, mannan oligosaccharides) on growth performance, carcasses, and antibody titer in broilers. A total number of 360-day-old Ross broiler chicks were randomly divided into 9 groups in a 3 × 3 factorial arrangement. Nine broiler starter (0–21 d) and finisher (21–35 d) diets were formulated by using 3 levels of probiotics (0, 1, and 2 g/kg of feed) and 3 levels of MOS (0, 1, and 1.5 g/kg o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
79
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(97 citation statements)
references
References 34 publications
13
79
2
3
Order By: Relevance
“…Although, abdominal fat yield is not statistically different in all the dietary treatments, birds fed with L. reuteri have shown the lowest fat percentage when compared to other treatments, this result may be credited to the decreasing effect of probiotics on fat deposition [ 37 , 66 ]. These results are in contrast with the studies of Moreira et al [ 67 ] and Vargas Jr. et al [ 68 ] that found no differences in the carcass yield by administering probiotics, while Rehman et al [ 69 ] concluded that supplementation of prebiotics or probiotics can improve the growth performance of broilers, Yousefi and Karkoodi, [ 70 ] and Sarangi et al [ 71 ] reported contradicting findings; weight gain was not affected by supplementation of probiotics in broiler diet. In this study, we discovered that S. coelicolor possessed beneficial effects on carcass percentage and breast percentage compared to all the other dietary treatments, while L. reuteri possessed positive effects on abdominal fat yield.…”
Section: Discussioncontrasting
confidence: 78%
“…Although, abdominal fat yield is not statistically different in all the dietary treatments, birds fed with L. reuteri have shown the lowest fat percentage when compared to other treatments, this result may be credited to the decreasing effect of probiotics on fat deposition [ 37 , 66 ]. These results are in contrast with the studies of Moreira et al [ 67 ] and Vargas Jr. et al [ 68 ] that found no differences in the carcass yield by administering probiotics, while Rehman et al [ 69 ] concluded that supplementation of prebiotics or probiotics can improve the growth performance of broilers, Yousefi and Karkoodi, [ 70 ] and Sarangi et al [ 71 ] reported contradicting findings; weight gain was not affected by supplementation of probiotics in broiler diet. In this study, we discovered that S. coelicolor possessed beneficial effects on carcass percentage and breast percentage compared to all the other dietary treatments, while L. reuteri possessed positive effects on abdominal fat yield.…”
Section: Discussioncontrasting
confidence: 78%
“…Saccharomyces cerevisiae is a rich source of enzymes, vitamins and other unknown cofactors that increase the activity of microbes in the rumen [5,6]. It also has a good amino acids profile and is endowed with prebiotic activity [7][8][9]. It also has the ability to compensate vitamin and amino acid deficiencies [10].…”
Section: Introductionmentioning
confidence: 99%
“…Hooge (2004) showed that MOS inclusion in broilers’ diets significantly boosted body weight and FCR and reduced mortality compared to the nonsupplemented diet. The inclusion of MOS in diets as a prebiotic could increase broilers’ growth rate ( Rehman et al., 2020 ). However, when comparing the antibiotics to MOS, there were no significant differences in birds’ body weight and FCR ( Ricke, 2015 , 2018 ; Micciche et al., 2018 ; Kim et al., 2019 ).…”
Section: Some Prebiotics Used To Improve Poultry Productionmentioning
confidence: 99%
“…The diet is the primary influence on the microbial profile and its encoded functions, affecting it toward the preferred trend ( Rehman et al., 2020 ). While the diet has been formulated for the poultry's nutritional needs, its capacity to influence metabolically active microorganisms has been overlooked ( Apajalahti and Vienola, 2016 ).…”
Section: Impacts Of Prebiotics On the Gut Structure Of Birdsmentioning
confidence: 99%